Project Yostate: creating a stylish online clothing store (MMIT Proceedings, 2025)
This article presents the YOSTATE project—a modern online store targeting a youth audience and street fashion enthusiasts. The core focus is on simplicity and clean design, allowing the products to take center stage and creating a premium atmosphere. The project implementation utilized the classical Waterfall model for planning and management. The web platform was developed using contemporary technologies: HTML, CSS, and JavaScript for the frontend, with plans to employ Node.js with Express and MongoDB for the backend. The article also includes a DFD diagram of the purchasing system, the application of the IDEF0 methodology for modeling functional processes, and an analysis of UML diagrams. The result is an intuitive interface with responsive design, ensuring easy navigation and high performance.